Synthesis of New Pyrazolo[1,5-a]pyrimidine, Triazolo[4,3-a]pyrimidine Derivatives, and Thieno[2,3-b]pyridine Derivatives from Sodium 3-(5-Methyl-1-phenyl-1H-pyrazol-4-yl)-3-oxoprop-1-en-1-olate - Abdou O. Abdelhamid; Sobhi M. Gomha (Journal of Chemistry)
Condensation of sodium 3-oxo-3-(1-phenyl-1H-pyrazol-4-yl)prop-1-en-1-olate (2) with several heterocyclic amines, cyanoacetamide, cyanothioacetamide, and 2-cyanoacetohydrazide gives pyrazolo[1,5-a]pyrimidines (5a–d), pyrido[2′,3′:3,4]pyrazolo[1,5-a]pyrimidine (9), benzo[4,5]imidazo[1,2-a]pyrimidine (10), [1,2,4]triazolo[1,5-a]pyrimidine (11), and pyridine derivatives (12–14). Also, thieno[2,3-b]pyridines (15–18) were synthesized via pyridinethione (13) with α-halo ketones and α-halo ester. Structures of the newly synthesized compounds were elucidated by elemental analysis, spectral data, alternative synthetic routes, and chemical transformation whenever possible.